Targeting delta opioid receptors for pain treatment: drugs in phase I and II clinical development. (1st February 2017) - Spahn, Viola; Stein, Christoph
ABSTRACT: Introduction : Opioids are widely used to treat severe pain. Most clinically used opioids activate µ-opioid receptors (MOR). Their ligands induce potent analgesia but also adverse effects. The δ-opioid receptor (DOR) is another member of the opioid receptor family that has been under intense investigation with the aim to avoid MOR-induced side effects. Areas covered : This article reviews DOR ligands which appeared to be promising after preclinical evaluation. A literature search using Pubmed, Cochrane library, ClinicalTrials.gov, EudraCT, AdisInsight database and EBSCO Online Library was conducted. Out of numerous newly synthesized molecules, only few candidates entered phase I and/or II clinical investigation. The publicly accessible results are presented here. Expert opinion : Many compounds showed potent DOR-specific pain inhibition in preclinical studies. ADL5859 and ADL5747 entered clinical trials and successfully passed phase I. However, in phase II studies the primary endpoint (pain reduction) was not met and further investigation was terminated. A third compound, NP2, is in phase II clinical evaluation and results are pending. These findings suggest a potential of DOR ligands according to preclinical studies. Further clinical research and secondary analysis of unpublished data is needed to identify molecules which are useful in humans.